Resident Endothelial Progenitor Cells From Human Placenta Have Greater Vasculogenic Potential Than Circulating Endothelial Progenitor Cells From Umbilical Cord Blood - Rapp, Brian M. (Cell Med, 2011)
Endothelial colony-forming cells (ECFCs) isolated from umbilical cord blood (CBECFCs) are highly proliferative and form blood vessels in vivo. The purpose of this investigation was to isolate and characterize a population of resident ECFCs from the chorionic villi of term human placenta and provide a comparative analysis of their proliferative and vasculogenic potential with CBECFCs. ECFCs were isolated from umbilical cord blood and chorionic villi from placentas obtained by caesarean deliveries. Placental ECFCs (PECFCs) expressed CD144, CD31, CD105, and KDR and were negative for CD45 and CD34, consistent with other ECFC phenotypes. PECFCs were capable of 28.6 ± 6.0 population doublings before reaching senescence (vs. 47.4 ± 3.2 for CBECFCs, p < 0.05, n = 4). In single cell assays, 46.5 ± 1.2% underwent at least one division (vs. 51.0 ± 1.8% of CBECFCs, p = 0.07, n = 6), and of those dividing PECFCs, 71.8 ± 0.9% gave rise to colonies of >500 cells (highly proliferative potential clones) over 14 days (vs. 69.4 ± 0.7% of CBECFCs, p = 0.07, n = 9). PECFCs formed 5.2 ± 0.8 vessels/mm(2) in collagen/fibronectin plugs implanted into non-obese diabetic/severe combined immunodeficient (NOD/SCID) mice, whereas CBECFCs formed only 1.7 ± 1.0 vessels/mm(2) (p < 0.05, n = 4). This study demonstrates that circulating CBECFCs and resident PECFCs are identical phenotypically and contain equivalent quantities of high proliferative potential clones. However, PECFCs formed significantly more blood vessels in vivo than CBECFCs, indicating that differences in vasculogenic potential between circulating and resident ECFCs exist.